Challenges and shifting treatment strategies in the surgical treatment of locally advanced rectal cancer. Issue 4 (11th June 2020) - Kim, Ho Seung; Kim, Nam Kyu
Abstract: The current standard treatment for locally advanced rectal cancer (LARC) in Korea and Western countries is a multimodal approach incorporating preoperative long‐course chemoradiotherapy (LCRT) followed by total mesorectal excision (TME) and adjuvant chemotherapy. This approach has significantly improved local control and reduced recurrence rates; however, the overall survival benefit has not been established. Although LCRT is a good option, there remain challenging unresolved problems for colorectal surgeons. We focused on four challenging issues in this review article. The first is LARC with resectable liver metastases, for which there has been no consensus regarding optimal management and practice thus far. The second is cancer progression at the time of restaging after completion of preoperative LCRT. To date, there have been few reports on this issue. The third is early recurrence after TME following preoperative LCRT, the reason for which is thought to be the delayed systemic chemotherapy in the preoperative LCRT protocol. The fourth is cost‐effectiveness. The preoperative LCRT protocol takes 5 weeks. After a 6‐8‐week waiting period, surgery is performed. Therefore, it is more time‐consuming than short‐course chemoradiotherapy. To overcome these issues, total neoadjuvant treatment (TNT) modalities, performed using various protocols, have been conducted globally based on cumulative experience. We also attempted to discuss previous TNT protocols in this article. One treatment strategy is not sufficient for patients with varying clinical characteristics. Therefore, we should revisit current treatment strategies based on recent clinical experience. Abstract : One treatment strategy is not sufficient for patients with locally advanced rectal cancer. We should revisit current treatment strategies based on recent clinical experience.